Should age be a factor in treatment choice of periprosthetic Vancouver B2-B3 proximal femur fractures? A retrospective analysis of mortality and functional outcomes in elderly patients - Canton, Gianluca; Rasio, Nicholas; Garlatti, Mauro; Ratti, Chiara; Kristan, Anže; Murena, Luigi (Acta Biomedica Atenei Parmensis, 2022)
Background and aim of the work Revision Arthroplasty (RA) is considered the treatment of choice for periprosthetic femur fractures (PFF) presenting with a loose stem. In the elderly RA may be associated with high post-operative mortality and complications. The aim of this study is to compare mortality and functional outcomes of open reduction internal fixation (ORIF) and RA for B2-B3 PFF in the elderly.Methods The study population included 29 patients (>65 years) surgically treated for B2-B3 PFF at the Orthopedic and Traumatology Unit of Cattinara University Hospital in Trieste (Italy) between January 2015 and December 2019. 16 patients were treated with ORIF and 13 with RA. Mortality and functional outcomes were analyzed.Results In-hospital (6,25% vs 7,69%) and 3 months (6,25 vs 15,38%) mortality was higher in the RA group. Mortality rates were particularly high in the > 85-year-old patients within four months from RA treatment. One year (38,46% and 16,67%) and overall mortality (69,22% and 25%) was higher after ORIF. Average time to weight-bearing and ambulation was 2.6 and 5.25 months for ORIF patients and 1.3 and 2.4 months for RA. A correlation was found between delayed weight-bearing and overall mortality.Conclusions Age is a risk factor for short term mortality following RA. Patients >85 years of age could benefit from a less invasive procedure such as ORIF. Long term outcomes are generally better for patients who undergo RA but further studies are necessary to evaluate the risk-benefit ratio of RA treatment compared to ORIF in elderly patients.